Trade Creation dan Trade Diversion Indonesia dengan AANZFTA pada Komoditas Garam - Nugraha, Dwi Tjahya; Irawan, Tony; Hakim, Dedi Budiman (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
ASEAN-Australia-New Zealand Free Trade Area (AANZFTA) is a free trade area formed in 2009. One of its implementations is the reduction of import duties on salt commodities in 2011. Its implementations has an impact on trade creation (TC) members and trade diversion (TD) on salt commodities product. The objective of this study is to analyze the occurrence TC and TD on salt commodity. Import demand elasticity and substitution elasticity approach for TC and TD estimation models was developed by the World Bank. The result is no all AANZFTA’s members get profit in the form of TC but just TD with dominated by Australia (99%) and other member (1%).